2017
DOI: 10.22219/jpbi.v3i3.4597
|View full text |Cite
|
Sign up to set email alerts
|

Improving of scientific literacy ability using discovery learning model at the seventh grade students of state JHS 3 Ngronggot, Nganjuk-Indonesia

Abstract: Country with good education condition can be seen through its citizen scientific literacy. This research aims to improving the students’ scientific literacy ability by using discovery learning model at 7th grade students of State Junior High School 3 Ngronggot, Nganjuk-Indonesia. The instrument in this Kemmis and Taggart Model of Classroom Action Research was an essay test composed based on indicators developed by Gormaly. The results of the research showed that there were improvements on the students’ scienti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
0
6
0
3
Order By: Relevance
“…• There is no significant difference in the improvement of students' science process skills between shared or webbed integration. (Dewi et al, 2017) The research subject were students in the seventh grade of SMP Negeri 3 Ngronggot Nganjuk.…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…• There is no significant difference in the improvement of students' science process skills between shared or webbed integration. (Dewi et al, 2017) The research subject were students in the seventh grade of SMP Negeri 3 Ngronggot Nganjuk.…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…Jenis model pembelajaran yang paling mudah dirancang oleh guru untuk membelajarkan literasi sains kepada siswa adalah model discovery learning, hal ini dikarenakan model pembelajaran tersebut mampu melatih siswa untuk melakukan kerja ilmiah seperti mengidentifikasi masalah dan bekerja sama untuk merancang solusi terhadap permasalahan yang ada. Hal tersebut sesuai dengan (Dewi et al, 2017) yang menyatakan bahwa model pembelajaran discovery learning memang telah terbukti dapat meningkatkan literasi sains pada siswa SMP terutama pada mata pelajaran IPA. Model pembelajaran yang dipilih guru merupakan model pembelajaran dengan pendekatan saintifik.…”
Section: Metode Kegiatanunclassified
“…In addition to viewing text, pictures, and animated videos, students can also process this information through group activities. Dewi et al, (2017) explained that Discovery Learning is a learning model that can facilitate students in understanding scientific information.…”
Section: Limited Trial Of Discovery Learning-based Animated Media On the Materials Of The Human Circulatory Systemmentioning
confidence: 99%
“…The Discovery Learning learning model consists of several phases, namely, stimulation or stimulation, problem identification, data collection, data processing, verification or proof, concluding (Sudarmin, 2015). In their research, Dewi et al, (2017) found that Discovery Learning is a learning model that can improve students' scientific literacy. Problem-solving activities in learning activities will have implications for the emergence of curiosity, high attitudes, and sensitivity for students (Astuti et al, 2017).…”
Section: Introductionmentioning
confidence: 99%